The Prominent Csángó Hub: Key Actors in the Network Structure of the Csángó Elite - Bodor-EranusEliza; Kónya, Hanna (Szociológiai Szemle, 2023)
The main question this article addresses is what characteristics should actors have to be recognized as prominent figures by the Csángó minority in the collaborating network of “Csángó matter”. To answer the question, we have analyzed the relations between actors – individuals and organizations – of this ethnic minority. The results show that a small and prominent hub of the Csángó elite has a remarkable role within the collaboration network of the “Csángó matter”, and their network position correlates with the interlock organizational membership as well.